Relevance of Education To Boarding Schools and Public Schools In The 4.0 Era - Wahyuddin Hamid; St Haniah; Nursalam Nursalam (Journal Research of Social Science, Economics, and Management, 2023)
This research was conducted at the DDI Mattoanging Bantaeng Islamic Boarding School and the Nurus Izzah Bantaeng Integrated Islamic School. This type of research is descriptive qualitative with a total of 16 informants from two schools. This study aims to see how far the government's efforts are in implementing education so that it is relevant in accordance with the 4.0 era. This evaluation will be carried out on the school's vision and mission, implementation of learning, and planting character education in students. The results of the study show that the relevance of education to religious-based Islamic boarding schools and general public in the 4.0 era has quite a few pros and cons. Where some people's perceptions see that the 4.0 era requires a moral foundation and religious values ??which are increasingly being eroded by cultural acculturation both from within the country and from abroad. However, the curriculum in education at Islamic boarding schools, which incidentally focuses on religious learning, is considered by some people to be less relevant to current conditions. Where the digitalis-based 4.0 era is seen as less capable of making students ready to face the world of classroom work. In contrast to public schools which are considered to be abreast of current technological developments, they also face obstacles in filtering students so they don't fully consume information that is considered too fast and this then has an impact on the development of children's learning competencies.